PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIEROPA SMP JUARA PEKANBARU T.A 2013/2014 - Al Razi Izzatul Yazid; Syofni Syofni; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The research was classroom action research that aims to improve learning process and mathematics learning outcomes with applied the cooperative learning type of think pair square (TPS). The subject of the research is students of class VIIIEropa SMP Juara Pekanbaru in the second semester academic years 2013/2014. There are 22 students in the class, consist of 11 boys and 11 girls who have heterogeneous academic ability. The research are two cycles, each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle of daily tests carried out. Data collected through observation and tests in the form of daily tests. Data analysis was performed with narrative descriptive analysis and descriptive statistical analysis. Results of this research showed that the teacher’s activities and students have done well after doing the action. Most of students were excited and active in learning process. Such as while they were doing the steps of learning, presenting students’ worksheet or questions, responding the friend’s presentation and giving the conclusion of learning. The action is successful if the number of students who achieve a score of minimum mastery criteria increase in daily tests I and II. The number of students who achieve a score of minimum mastery criteria on basic, daily test I (first cycle) and daily test II (second cycle) are respectively 13.63%, 40.91%, and 86.63%. Results of this research indicates that the cooperative learning type of think pair square can improve learning process and students' mathematics learning outcomes math class VIIIEropa SMP Juara Pekanbaru.Key words: Mathematics learning outcome, Cooperative learning, Think Pair Square, Class action research